Aluminum-steel composite structure cmt fusion welding material and method
Patent Information
- Application Number
- CN202311342159.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-10-17
AI Technical Summary
爆炸焊接是制备大尺寸铝-钢复合板的理想选择,对于一些小结构件,则无法通过保证焊接的方式制备;电阻点焊只适合于一些薄板结构件的焊接;扩散焊只能连接规则形状的铝-钢结构件
[0024](1)本发明材料为镍基药芯焊丝,以Ni元素为主,根据Ni-Fe二元相图可知,Ni与Fe之间结合良好,并且两者熔点接近,可以保证较好的结合强度。
Smart Images

Figure CN117464240B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal material welding technology, specifically relating to a material for CMT fusion welding of aluminum-steel composite structures. This invention also relates to a method for preparing the material for CMT fusion welding of aluminum-steel composite structures and a method for preparing aluminum-steel composite structures using the material for CMT fusion welding of aluminum-steel composite structures. Background Technology
[0002] Lightweight design has become a consensus in industries such as automotive manufacturing and aerospace. Aluminum and its alloys have advantages such as low specific gravity, excellent corrosion resistance, good thermal conductivity, low density, and high specific strength, while steel has high strength and high creep resistance. Therefore, aluminum-steel dissimilar structural components are an ideal choice for achieving lightweight design in automobiles and aircraft. However, when aluminum and steel are directly fused and welded, brittle Fe-Al intermetallic compounds are prone to form, leading to joint cracking. In addition, the melting point of aluminum is much lower than that of steel, resulting in poor joint formation when the two are directly welded.
[0003] Currently, direct aluminum-steel joining typically employs solid-state welding methods, such as explosive welding, resistance spot welding, and diffusion welding. Explosive welding is ideal for fabricating large-sized aluminum-steel composite plates, but it cannot be used to fabricate some small structural components. Resistance spot welding is only suitable for welding thin-plate structural components. Diffusion welding can only join aluminum-steel structural components with regular shapes. Fusion welding is a flexible welding method that can fabricate structural components of various shapes and sizes; however, using fusion welding for aluminum-steel structural components requires addressing issues such as the formation of brittle phases at the joint and poor joint formation. Summary of the Invention
[0004] The first objective of this invention is to provide a material for CMT welding of aluminum-steel composite structures, which can solve the problems of brittle phase formation and poor forming during the preparation of aluminum-steel composite structures.
[0005] The second objective of this invention is to provide a method for preparing materials for aluminum-steel composite CMT welding.
[0006] The third objective of this invention is to provide a method for preparing an aluminum-steel composite structure using materials for CMT fusion welding of aluminum-steel composite structures.
[0007] The first technical solution adopted in this invention is a material for CMT fusion welding of aluminum-steel composite structures, including a flux core and a weld skin, wherein the flux core is composed of the following components by mass percentage: 40-50% Zn powder, 20-30% Cr powder, 10-15% Mn powder, 0.5-1% Y powder, and the balance is Ni powder, and the sum of the mass percentages of the above components is 100%.
[0008] The invention is further characterized in that,
[0009] The purity of each core powder is greater than 99.9%.
[0010] The nickel strip is 0.3mm thick and 7mm wide.
[0011] The filling amount of flux-cored welding wire is controlled at 20wt% to 25wt%.
[0012] The second technical solution adopted in this invention is a method for preparing the above-mentioned aluminum-steel composite structure CMT fusion welding material, the specific steps of which are as follows:
[0013] Step 1: Weigh out 40-50% Zn powder, 20-30% Cr powder, 10-15% Mn powder, 0.5-1% Y powder by mass percentage, with the remainder being Ni powder. The sum of the mass percentages of the above components is 100%.
[0014] Step 2: Place the alloy powder weighed in Step 1 into a vacuum heating furnace for heating and holding at a temperature of 100℃-150℃ for 1-2 hours; place the dried powder into a powder mixer for thorough mixing for 1-2 hours.
[0015] Step 3: Use alcohol to remove the grease from the surface of the pure nickel strip, and use a flux-cored wire drawing machine to wrap the flux powder prepared in step 2 inside the nickel strip. The diameter of the first drawing die is 2.6mm.
[0016] Step 4: After the first drawing process is completed, the die hole diameter is changed to 2.3mm, 2.0mm, 1.8mm, 1.6mm, 1.4mm and 1.2mm in sequence for drawing. The final diameter of the flux-cored welding wire is 1.2mm.
[0017] Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use; the filling amount of flux-cored welding wire powder is controlled at 20wt% to 25wt%.
[0018] The third technical solution adopted in this invention is a method for preparing an aluminum-steel composite structure using the aforementioned aluminum-steel composite CMT fusion welding material, the specific method of which is as follows:
[0019] (1) Grind the surface of the steel plate with a wire brush to remove the oxide scale, and wipe it with alcohol to remove the oil stains;
[0020] (2) The above-mentioned aluminum-steel composite CMT fusion welding material is used to weld on the steel plate to obtain a nickel-based weld overlay. The welding power source is a CMT power source with a welding current of 180A to 200A. The shielding gas is a mixed gas, which is composed of the following components by volume percentage: 98% Ar and 2% O2, and the sum of the volume percentages of the above components is 100%. The swing width is 10mm to 20mm and the single layer thickness is 2.0mm to 2.5mm.
[0021] (3) The first aluminum overlay layer is obtained by overlaying aluminum wire on the nickel-based overlay layer obtained in step (2). The aluminum wire grade is ER4043. The welding power source is CMT power source. The welding current of the first aluminum overlay layer is 55A~65A, the voltage is 10V~12V, the welding speed is 50cm / s~60cm / s, the shielding gas is 100%Ar, no oscillation, and the single layer thickness is 2.0mm~2.5mm.
[0022] (4) Continue to weld aluminum wire on the first aluminum overlay layer obtained in step (3). The aluminum wire grade is ER4043. The welding power source is CMT power source. The parameters of the second aluminum overlay layer and subsequent aluminum overlay layers are the same, specifically: welding current 75A~85A, voltage 11V~13V, welding speed 40cm / s~50cm / s, shielding gas is 100%Ar, swing width 3.5mm~4.5mm, and single layer thickness 3.0mm~3.5mm.
[0023] The beneficial effects of this invention are:
[0024] (1) The material of this invention is nickel-based flux-cored welding wire, mainly composed of Ni element. According to the Ni-Fe binary phase diagram, Ni and Fe are well bonded and their melting points are close, which can ensure good bonding strength.
[0025] (2) The nickel-based flux-cored welding wire of the present invention mainly contains Zn and Cr elements: Zn and Cr have high solid solubility in nickel-based alloys, and Zn and Cr also have high solid solubility with Fe. The welding wire is mainly composed of Zn and Cr, which can ensure excellent bonding with the base steel. The addition of Zn can effectively reduce the melting point of the weld, thereby ensuring uniform droplet transfer, less spatter, and better spread of the molten pool and base metal during CMT welding, and finally effectively improving the weld formation and solving the problem of poor formation.
[0026] (3) This invention employs CMT (Cold Metal Transfer) technology to weld the nickel-based transition layer and the aluminum welding wire on top, ensuring a low dilution rate and excellent formability. Especially when welding the aluminum welding wire onto the nickel-based overlay layer, due to the low solid solubility between Ni and Al and the low melting point of Al, the CMT welding process can achieve almost the effect of brazing, thus ensuring good bonding quality at the aluminum / nickel interface. Using this material can solve the problems of brittle phase formation and poor formability in the preparation of aluminum-steel composite structures.
[0027] (4) The flux-cored welding wire of the present invention has fewer alloy elements, the preparation process is simple, and it is easy to carry out large-scale mass production. Attached Figure Description
[0028] Figure 1 A schematic diagram of the process for preparing aluminum-steel composite structures using materials for CMT fusion welding of aluminum-steel composite structures;
[0029] Figure 2 The microstructure of the steel matrix / nickel-based weld interface when the nickel-based flux-cored wire prepared in Example 2 of this invention is welded on steel;
[0030] Figure 3 The microstructure of the nickel-based weld when the nickel-based flux-cored wire prepared in Example 2 of this invention is welded on steel. Detailed Implementation
[0031] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.
[0032] This invention provides a material for CMT fusion welding of aluminum-steel composite structures, comprising a flux core and a weld skin, wherein the flux core is composed of the following components by mass percentage: 40-50% Zn powder, 20-30% Cr powder, 10-15% Mn powder, 0.5-1% Y powder, and the balance being Ni powder, and the sum of the mass percentages of the above components is 100%.
[0033] The purity of each core powder is greater than 99.9%, and the particle size of the powder is 200-300 mesh.
[0034] The solder sheet is made of pure nickel strip, with a thickness of 0.3 mm and a width of 7 mm.
[0035] The filling amount of flux-cored welding wire is controlled at 20wt% to 25wt%.
[0036] The roles and functions of each component in this flux-cored welding wire are as follows:
[0037] (1) Ni is the main component of flux-cored welding wire. As shown in the Fe-Ni binary phase diagram, Ni and Fe can dissolve indefinitely at high temperatures, forming an austenitic structure. Therefore, using Ni as the main component of the welding wire ensures a good metallurgical bond between the nickel-based weld overlay and the base steel plate. Furthermore, according to the Ni-Al binary phase diagram, the maximum solubility of Al in Ni can reach 11%, indicating a relatively high solubility. Ni has a melting point of 1455℃, while Al has a melting point of 660℃, a significant difference. Therefore, when welding Al onto Ni, using CMT (Cold Metal Transfer) technology can ensure effective brazing (Al welding wire melts, but the Ni-based weld overlay does not), thus preventing the formation of brittle phases between Ni and Al and improving the interfacial bonding quality.
[0038] Zn is the main component of the welding wire flux. According to the Fe-Zn binary phase diagram, Zn has a high solid solubility in Fe, ensuring good bonding between the steel matrix and the nickel-based transition layer. According to the Al-Zn binary phase diagram, both have very high solid solubility at high temperatures, with up to 83.1% of Zn dissolveable in Al. Furthermore, Zn's melting point is 419℃, lower than that of Al. Therefore, adding Zn to the welding wire flux, through its reaction with Al, can lower the melting point of the welding wire, improve the fluidity of the liquid weld metal, and further facilitate subsequent brazing.
[0039] As a major component of the flux powder, Cr has a high solid solubility in Fe, as shown in the Fe-Cr binary phase diagram. Cr is a commonly used additive element in steel materials, which can not only improve the strength of steel through solid solution strengthening but also improve the corrosion resistance of welds. However, brittle intermetallic compounds can form between Al and Cr, therefore, the addition of Cr to the weld needs to be controlled.
[0040] As a key component of fluxing agents, manganese (Mn) is a commonly used additive element in steel materials. On one hand, it enhances weld strength through solid solution strengthening; on the other hand, it helps deoxidize and desulfurize the weld, thereby reducing weld defects. According to the Mn-Ni binary phase diagram, Ni contains a relatively high amount of Mn that can be dissolved (up to 28%). Therefore, the addition of Mn can also improve the strength of nickel-based welds.
[0041] Y element is added in small amounts to the flux-cored wire. As a rare earth element, Y can effectively refine the grains of nickel-based single-phase welds due to their coarse grains, and it also helps to purify grain boundaries and improve grain boundary bonding strength. According to the Al-Y binary phase diagram, the amount of Y that can be dissolved in Al is relatively small; therefore, Y is also added in small amounts to the flux-cored wire.
[0042] This invention also provides a method for preparing the above-mentioned aluminum-steel composite CMT fusion welding material, the specific steps of which are as follows:
[0043] Step 1: Weigh out 40-50% Zn powder, 20-30% Cr powder, 10-15% Mn powder, 0.5-1% Y powder by mass percentage, with the remainder being Ni powder. The sum of the mass percentages of the above components is 100%.
[0044] Step 2: Place the alloy powder weighed in Step 1 into a vacuum heating furnace for heating and heat preservation to remove the water of crystallization in the powder. The heating temperature in the vacuum heating furnace is 100℃-150℃, and the heat preservation time is 1h-2h. After drying, place the powder into a powder mixer for thorough mixing. The mixing time in the powder mixer is 1h-2h.
[0045] Step 3: Use alcohol to remove the grease from the surface of the pure nickel strip, and use a flux-cored wire drawing machine to wrap the flux powder prepared in step 2 inside the nickel strip. The diameter of the first drawing die is 2.6mm.
[0046] Step 4: After the first drawing process is completed, the die hole diameter is changed to 2.3mm, 2.0mm, 1.8mm, 1.6mm, 1.4mm and 1.2mm in sequence for drawing. The final diameter of the flux-cored welding wire is 1.2mm.
[0047] Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use; the filling amount of flux-cored welding wire powder is controlled at 20wt% to 25wt%.
[0048] This invention also provides a method for preparing an aluminum-steel composite structure using the above-mentioned aluminum-steel composite CMT welding material, the specific method of which is as follows: Figure 1 As shown:
[0049] (1) Grind the surface of the steel plate with a wire brush to remove the oxide scale, and wipe it with alcohol to remove the oil stains;
[0050] (2) The above-mentioned aluminum-steel composite CMT fusion welding material is used to weld on the steel plate to obtain a nickel-based weld overlay. The welding power source is a CMT power source with a welding current of 180A to 200A. The shielding gas is a mixed gas, which is composed of the following components by volume percentage: 98% Ar and 2% O2, and the sum of the volume percentages of the above components is 100%. The swing width is 10mm to 20mm and the single layer thickness is 2.0mm to 2.5mm.
[0051] (3) The first aluminum overlay layer is obtained by overlaying aluminum wire on the nickel-based overlay layer obtained in step (2). The aluminum wire grade is ER4043. The welding power source is CMT power source. The welding current of the first aluminum overlay layer is 55A~65A, the voltage is 10V~12V, the welding speed is 50cm / s~60cm / s, the shielding gas is 100%Ar, no oscillation, and the single layer thickness is 2.0mm~2.5mm.
[0052] (4) Continue to weld aluminum wire on the first aluminum overlay layer obtained in step (3). The aluminum wire grade is ER4043. The welding power source is CMT power source. The parameters of the second aluminum overlay layer and subsequent aluminum overlay layers are the same, specifically: welding current 75A~85A, voltage 11V~13V, welding speed 40cm / s~50cm / s, shielding gas is 100%Ar, swing width 3.5mm~4.5mm, and single layer thickness 3.0mm~3.5mm.
[0053] Example 1
[0054] Step 1: Weigh out 40% Zn powder, 20% Cr powder, 10% Mn powder, and 0.5% Y powder by mass percentage, with the remainder being Ni powder. The sum of the mass percentages of the above components is 100%. The purity of each core powder is greater than 99.9%, and the particle size of the powder is 200 mesh.
[0055] Step 2: Place the alloy powder weighed in Step 1 into a vacuum heating furnace for heating and heat preservation to remove the water of crystallization in the powder. The heating temperature in the vacuum heating furnace is 100℃ and the heat preservation time is 1 hour. After drying, place the powder into a powder mixer for thorough mixing. The mixing time in the powder mixer is 1 hour.
[0056] Step 3: Use alcohol to remove the grease from the surface of the pure nickel strip, and use a flux-cored wire drawing machine to wrap the flux powder prepared in step 2 inside the nickel strip. The diameter of the first drawing die is 2.6 mm; the nickel strip is 0.3 mm thick and 7 mm wide.
[0057] Step 4: After the first drawing process is completed, the die hole diameter is changed to 2.3mm, 2.0mm, 1.8mm, 1.6mm, 1.4mm and 1.2mm in sequence for drawing. The final diameter of the flux-cored welding wire is 1.2mm.
[0058] Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use; the filling amount of flux-cored welding wire powder is controlled at 20wt%.
[0059] The nickel-based flux-cored welding wire prepared in Example 1 was used to prepare aluminum-steel composite CMT fusion welding, and the specific method (e.g.) Figure 1 As shown):
[0060] (1) Grind the surface of the steel plate with a wire brush to remove the oxide scale, and wipe it with alcohol to remove the oil stains;
[0061] (2) Welding is performed on steel plates using the nickel-based welding wire of the present invention. The welding power source is a CMT power source with a welding current of 180-200A. The shielding gas is a mixed gas, which is composed of the following components by volume percentage: 98% Ar and 2% O2, and the sum of the volume percentages of the above components is 100%. The swing width is 10mm and the single layer thickness is 2.0mm.
[0062] (3) Aluminum welding wire is welded onto the nickel-based weld overlay obtained in step (2) to obtain the first aluminum weld overlay. The aluminum welding wire grade is ER4043. The welding power source is CMT power source: the first layer welding current is 55-65A, the voltage is 10-12V, the welding speed is 50cm / s, the shielding gas is 100%Ar, no oscillation, and the single layer thickness is 2.5mm.
[0063] (4) Continue to weld aluminum welding wire on the first aluminum overlay layer obtained in step (3). The aluminum welding wire grade is ER4043. The welding power source is CMT power source. The parameters of the second aluminum overlay layer and subsequent aluminum overlay layers are the same, specifically: welding current 75~85A, voltage 11~13V, welding speed 40cm / s, shielding gas is 100%Ar, swing width 3.5mm, and single layer thickness 3.5mm.
[0064] The test results of the aluminum-steel composite structure obtained by the above welding are as follows:
[0065] (1) The joint was inspected by X-ray and no cracks or pores were found;
[0066] (2) The nickel-based weld is mainly composed of single-phase austenitic structure, and the nickel-based weld has good bonding with the steel matrix and aluminum weld.
[0067] (3) Tensile test specimens of the joint were prepared. The test results showed that the tensile strength of the joint was 261 MPa, the elongation after fracture was 25%, and the fracture location was at the Al weld.
[0068] Example 2
[0069] Step 1: Weigh out 50% Zn powder, 30% Cr powder, 15% Mn powder, and 1% Y powder by mass percentage, with the remainder being Ni powder. The sum of the mass percentages of the above components is 100%. The purity of each core powder is greater than 99.9%, and the particle size of the powder is 300 mesh.
[0070] Step 2: Place the alloy powder weighed in Step 1 into a vacuum heating furnace for heating and heat preservation to remove the water of crystallization in the powder. The heating temperature in the vacuum heating furnace is 150℃ and the heat preservation time is 2 hours. After drying, place the powder into a powder mixer for thorough mixing. The mixing time in the powder mixer is 2 hours.
[0071] Step 3: Use alcohol to remove the grease from the surface of the pure nickel strip, and use a flux-cored wire drawing machine to wrap the flux powder prepared in step 2 inside the nickel strip. The diameter of the first drawing die is 2.6 mm; the nickel strip is 0.3 mm thick and 7 mm wide.
[0072] Step 4: After the first drawing process is completed, the die hole diameter is changed to 2.3mm, 2.0mm, 1.8mm, 1.6mm, 1.4mm and 1.2mm in sequence for drawing. The final diameter of the flux-cored welding wire is 1.2mm.
[0073] Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use; the filling amount of flux-cored welding wire powder is controlled at 25wt%.
[0074] The nickel-based flux-cored welding wire prepared in Example 2 was used to prepare aluminum-steel composite CMT fusion welding, and the specific method (e.g.) Figure 1 As shown):
[0075] (1) Grind the surface of the steel plate with a wire brush to remove the oxide scale, and wipe it with alcohol to remove the oil stains;
[0076] (2) Welding is performed on steel plates using the nickel-based welding wire of the present invention. The welding power source is a CMT power source with a welding current of 180-200A. The shielding gas is a mixed gas, which is composed of the following components by volume percentage: 98% Ar and 2% O2, and the sum of the volume percentages of the above components is 100%. The swing width is 10-20mm and the single layer thickness is 2.5mm.
[0077] (3) Aluminum welding wire is welded onto the nickel-based weld overlay obtained in step (2) to obtain the first aluminum weld overlay. The aluminum welding wire grade is ER4043. The welding power source is CMT power source: the first layer welding current is 55-65A, the voltage is 10-12V, the welding speed is 60cm / s, the shielding gas is 100%Ar, no oscillation, and the single layer thickness is 2.0mm.
[0078] (4) Continue to weld aluminum wire on the first aluminum overlay layer obtained in step (3). The aluminum wire grade is ER4043. The welding power source is CMT power source. The parameters of the second aluminum overlay layer and subsequent aluminum overlay layers are the same, specifically: welding current 75~85A, voltage 11~13V, welding speed 50cm / s, shielding gas is 100%Ar, swing width 4.5mm, and single layer thickness 3.0mm.
[0079] The test results of the aluminum-steel composite structure obtained by the above welding are as follows:
[0080] (1) The joint was inspected by X-ray and no cracks or pores were found;
[0081] (2) The nickel-based weld is mainly composed of single-phase austenitic structure, and the nickel-based weld has good bonding with the steel matrix and aluminum weld.
[0082] (3) Tensile test specimens of the joint were prepared. The test results showed that the tensile strength of the joint was 272 MPa, the elongation after fracture was 24%, and the fracture location was at the Al weld.
[0083] Figure 2 The figure shows the microstructure of the interface between the steel plate and the nickel-based weld. It can be seen from the figure that the interface is well bonded and there are no cracks or porosity defects. Figure 3 The microstructure of the nickel-based weld is shown in the figure, which is dominated by single-phase austenite with fine and uniform grains. Using this material can solve the problem of poor brittle phase formation and shape during the fabrication of aluminum-steel composite structures.
[0084] Example 3
[0085] Step 1: Weigh out 45% Zn powder, 25% Cr powder, 13% Mn powder, and 0.7% Y powder by mass percentage, with the remainder being Ni powder. The sum of the mass percentages of the above components is 100%. The purity of each core powder is greater than 99.9%, and the particle size of the powder is 200 mesh.
[0086] Step 2: Place the alloy powder weighed in Step 1 into a vacuum heating furnace for heating and heat preservation to remove the water of crystallization in the powder. The heating temperature in the vacuum heating furnace is 130℃ and the heat preservation time is 1.5h. After drying, place the powder into a powder mixer for thorough mixing. The mixing time in the powder mixer is 1.5h.
[0087] Step 3: Use alcohol to remove the grease from the surface of the pure nickel strip, and use a flux-cored wire drawing machine to wrap the flux powder prepared in step 2 inside the nickel strip. The diameter of the first drawing die is 2.6 mm; the nickel strip is 0.3 mm thick and 7 mm wide.
[0088] Step 4: After the first drawing process is completed, the die hole diameter is changed to 2.3mm, 2.0mm, 1.8mm, 1.6mm, 1.4mm and 1.2mm in sequence for drawing. The final diameter of the flux-cored welding wire is 1.2mm.
[0089] Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use; the filling amount of flux-cored welding wire powder is controlled at 22wt%.
[0090] The nickel-based flux-cored welding wire prepared in Example 3 was used to prepare aluminum-steel composite CMT fusion welding, and the specific method (e.g.) Figure 1 As shown):
[0091] (1) Grind the surface of the steel plate with a wire brush to remove the oxide scale, and wipe it with alcohol to remove the oil stains;
[0092] (2) Welding is performed on steel plates using the nickel-based welding wire of the present invention. The welding power source is a CMT power source with a welding current of 180-200A. The shielding gas is a mixed gas, which is composed of the following components by volume percentage: 98% Ar and 2% O2, with the sum of the volume percentages of the above components being 100%. The swing width is 15mm and the single layer thickness is 2.3mm.
[0093] (3) Aluminum welding wire is welded onto the nickel-based weld overlay obtained in step (2) to obtain the first aluminum weld overlay. The aluminum welding wire grade is ER4043. The welding power source is CMT power source: the first layer welding current is 55-65A, the voltage is 10-12V, the welding speed is 55cm / s, the shielding gas is 100%Ar, no oscillation, and the single layer thickness is 2.3mm.
[0094] (4) Continue to weld aluminum wire on the first aluminum overlay layer obtained in step (3). The aluminum wire grade is ER4043. The welding power source is CMT power source. The parameters of the second aluminum overlay layer and subsequent aluminum overlay layers are the same, specifically: welding current 75~85A, voltage 11~13V, welding speed 45cm / s, shielding gas is 100%Ar, swing width 4.0mm, and single layer thickness 3.2mm.
[0095] The test results of the aluminum-steel composite structure obtained by the above welding are as follows:
[0096] (1) The joint was inspected by X-ray and no cracks or pores were found;
[0097] (2) The nickel-based weld is mainly composed of single-phase austenitic structure, and the nickel-based weld has good bonding with the steel matrix and aluminum weld.
[0098] (3) Tensile test specimens of the joint were prepared. The test results showed that the tensile strength of the joint was 255 MPa, the elongation after fracture was 27%, and the fracture location was at the Al weld.
[0099] Example 4
[0100] Step 1: Weigh out 47% Zn powder, 27% Cr powder, 12% Mn powder, and 0.6% Y powder by mass percentage, with the remainder being Ni powder. The sum of the mass percentages of the above components is 100%. The purity of each core powder is greater than 99.9%, and the particle size of the powder is 300 mesh.
[0101] Step 2: Place the alloy powder weighed in Step 1 into a vacuum heating furnace for heating and holding to remove the water of crystallization in the powder. The heating temperature in the vacuum heating furnace is 120℃ and the holding time is 1.2h. After drying, place the powder into a powder mixer for thorough mixing. The mixing time in the powder mixer is 1.2h.
[0102] Step 3: Use alcohol to remove the grease from the surface of the pure nickel strip, and use a flux-cored wire drawing machine to wrap the flux powder prepared in step 2 inside the nickel strip. The diameter of the first drawing die is 2.6 mm; the nickel strip is 0.3 mm thick and 7 mm wide.
[0103] Step 4: After the first drawing process is completed, the die hole diameter is changed to 2.3mm, 2.0mm, 1.8mm, 1.6mm, 1.4mm and 1.2mm in sequence for drawing. The final diameter of the flux-cored welding wire is 1.2mm.
[0104] Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use; the filling amount of flux-cored welding wire powder is controlled at 20wt%.
[0105] The nickel-based flux-cored welding wire prepared in Example 4 was used to prepare aluminum-steel composite CMT fusion welding, and the specific method (e.g.) Figure 1 As shown):
[0106] (1) Grind the surface of the steel plate with a wire brush to remove the oxide scale, and wipe it with alcohol to remove the oil stains;
[0107] (2) Welding is performed on steel plates using the nickel-based welding wire of the present invention. The welding power source is a CMT power source with a welding current of 180-200A. The shielding gas is a mixed gas, which is composed of the following components by volume percentage: 98% Ar and 2% O2, and the sum of the volume percentages of the above components is 100%. The swing width is 14mm and the single layer thickness is 2.2mm.
[0108] (3) Aluminum welding wire is welded onto the nickel-based weld overlay obtained in step (2) to obtain the first aluminum weld overlay. The aluminum welding wire grade is ER4043. The welding power source is CMT power source: the first layer welding current is 55-65A, the voltage is 10-12V, the welding speed is 56cm / s, the shielding gas is 100%Ar, no oscillation, and the single layer thickness is 2.2mm.
[0109] (4) Continue to weld aluminum wire on the first aluminum overlay layer obtained in step (3). The aluminum wire grade is ER4043. The welding power source is CMT power source. The parameters of the second aluminum overlay layer and subsequent aluminum overlay layers are the same, specifically: welding current 75~85A, voltage 11~13V, welding speed 47cm / s, shielding gas is 100%Ar, swing width 3.8mm, and single layer thickness 3.4mm.
[0110] The test results of the aluminum-steel composite structure obtained by the above welding are as follows:
[0111] (1) The joint was inspected by X-ray and no cracks or pores were found;
[0112] (2) The nickel-based weld is mainly composed of single-phase austenitic structure, and the nickel-based weld has good bonding with the steel matrix and aluminum weld.
[0113] (3) Tensile test specimens of the joint were prepared. The test results showed that the tensile strength of the joint was 280 MPa, the elongation after fracture was 23%, and the fracture location was at the Al weld.
[0114] Example 5
[0115] Step 1: Weigh out 41% Zn powder, 29% Cr powder, 14% Mn powder, and 0.65% Y powder by mass percentage, with the remainder being Ni powder. The sum of the mass percentages of the above components is 100%. The purity of each core powder is greater than 99.9%, and the particle size of the powder is 250 mesh.
[0116] Step 2: Place the alloy powder weighed in Step 1 into a vacuum heating furnace for heating and heat preservation to remove the water of crystallization in the powder. The heating temperature in the vacuum heating furnace is 145℃ and the heat preservation time is 1.45h. After drying, place the powder into a powder mixer for thorough mixing. The mixing time in the powder mixer is 1.35h.
[0117] Step 3: Use alcohol to remove the grease from the surface of the pure nickel strip, and use a flux-cored wire drawing machine to wrap the flux powder prepared in step 2 inside the nickel strip. The diameter of the first drawing die is 2.6 mm; the nickel strip is 0.3 mm thick and 7 mm wide.
[0118] Step 4: After the first drawing process is completed, the die hole diameter is changed to 2.3mm, 2.0mm, 1.8mm, 1.6mm, 1.4mm and 1.2mm in sequence for drawing. The final diameter of the flux-cored welding wire is 1.2mm.
[0119] Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use; the filling amount of flux-cored welding wire powder is controlled at 20wt%.
[0120] The nickel-based flux-cored welding wire prepared in Example 5 was used to prepare aluminum-steel composite CMT fusion welding, and the specific method (e.g.) Figure 1 As shown):
[0121] (1) Grind the surface of the steel plate with a wire brush to remove the oxide scale, and wipe it with alcohol to remove the oil stains;
[0122] (2) Welding is performed on steel plates using the nickel-based welding wire of the present invention. The welding power source is a CMT power source with a welding current of 180-200A. The shielding gas is a mixed gas, which is composed of the following components by volume percentage: 98% Ar and 2% O2, and the sum of the volume percentages of the above components is 100%. The swing width is 18mm and the single layer thickness is 2.1mm.
[0123] (3) Aluminum welding wire is welded onto the nickel-based weld overlay obtained in step (2) to obtain the first aluminum weld overlay. The aluminum welding wire grade is ER4043. The welding power source is CMT power source: the first layer welding current is 55-65A, the voltage is 10-12V, the welding speed is 52cm / s, the shielding gas is 100%Ar, no oscillation, and the single layer thickness is 2.45mm.
[0124] (4) Continue to weld aluminum wire on the first aluminum overlay layer obtained in step (3). The aluminum wire grade is ER4043. The welding power source is CMT power source. The parameters of the second aluminum overlay layer and subsequent aluminum overlay layers are the same, specifically: welding current 75~85A, voltage 11~13V, welding speed 41cm / s, shielding gas is 100%Ar, swing width 4.2mm, and single layer thickness 3.45mm.
[0125] The test results of the aluminum-steel composite structure obtained by the above welding are as follows:
[0126] (1) The joint was inspected by X-ray and no cracks or pores were found;
[0127] (2) The nickel-based weld is mainly composed of single-phase austenitic structure, and the nickel-based weld has good bonding with the steel matrix and aluminum weld.
[0128] (3) Tensile test specimens of the joint were prepared. The test results showed that the tensile strength of the joint was 266 MPa, the elongation after fracture was 25.5%, and the fracture location was at the Al weld.
Claims
1. A material for CMT fusion welding of aluminum-steel composite structures, characterized in that, It includes a flux core and a solder sheet. The flux core is composed of the following components by mass percentage: 40-50% Zn powder, 20-30% Cr powder, 10-15% Mn powder, 0.5-1% Y powder, and the balance is Ni powder. The sum of the mass percentages of the above components is 100%. The solder sheet is a pure nickel strip. The filling amount of flux core powder in the flux-cored welding wire is controlled at 20wt%-25wt%.
2. The material for CMT fusion welding of aluminum-steel composite structures according to claim 1, characterized in that, The purity of each core powder is greater than 99.9%.
3. The material for CMT fusion welding of aluminum-steel composite structures according to claim 1, characterized in that, The nickel strip is 0.3mm thick and 7mm wide.
4. The method for preparing the aluminum-steel composite structure CMT fusion welding material according to any one of claims 1-3, characterized in that, The specific steps are as follows: Step 1: Weigh out 40-50% Zn powder, 20-30% Cr powder, 10-15% Mn powder, and 0.5-1% Y powder by mass percentage, with the remainder being Ni powder. The sum of the mass percentages of the above components is 100%. Step 2: Place the alloy powder weighed in Step 1 into a vacuum heating furnace for heating and holding at a temperature of 100℃-150℃ for 1-2 hours; place the dried powder into a powder mixer for thorough mixing for 1-2 hours. Step 3: The flux powder prepared in step 2 is wrapped in nickel strip using a flux-cored wire drawing machine. The diameter of the first drawing die is 2.6 mm. Step 4: After the first drawing process is completed, the die hole diameter is changed to 2.3mm, 2.0mm, 1.8mm, 1.6mm, 1.4mm and 1.2mm in sequence for drawing. The final diameter of the flux-cored welding wire is 1.2mm. Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use; the filling amount of flux-cored welding wire is controlled at 20wt%~25wt%.
5. A method for preparing aluminum-steel composite structures using materials for CMT fusion welding of aluminum-steel composite structures, characterized in that, The specific method is as follows: (1) Polish the surface of the steel plate with a wire brush to remove oil stains; (2) The aluminum-steel composite structure CMT fusion welding material described in any one of claims 1-3 is used to weld a nickel-based weld overlay on a steel plate. The welding power source is a CMT power source with a welding current of 180A~200A. The shielding gas is a mixed gas, which is composed of the following components by volume percentage: 98%Ar and 2%O2, and the sum of the volume percentages of the above components is 100%. The swing width is 10mm~20mm and the single layer thickness is 2.0mm~2.5mm. (3) Aluminum welding wire is welded onto the nickel-based weld overlay obtained in step (2) to obtain the first aluminum weld overlay. The aluminum welding wire grade is ER4043. The welding power source is CMT power source. The welding current of the first aluminum weld overlay is 55A~65A, the voltage is 10V~12V, the welding speed is 50cm / s~60cm / s, the shielding gas is 100%Ar, no oscillation, and the single layer thickness is 2.0mm~2.5mm. (4) Continue to weld aluminum wire on the first aluminum overlay layer obtained in step (3). The aluminum wire grade is ER4043. The welding power source is CMT power source. The parameters of the second aluminum overlay layer and subsequent aluminum overlay layers are the same, specifically: welding current 75A~85A, voltage 11V~13V, welding speed 40cm / s~50cm / s, shielding gas is 100%Ar, swing width 3.5mm~4.5mm, and single layer thickness 3.0mm~3.5mm.
Citation Information
Patent Citations
Material and method for electric arc 3D printing of Fe-Al-Fe transition joint
CN114473287A